Emerging Regional Order: Implications for Pakistan’s Maritime Security - Muhammad Hasnain; Muhammad Owais; Ashfaq Ahmed (ASIAN Journal of International Peace & Security (AJIPS), 2021)
The present study attempts to assess the emerging regional order and its implications for Pakistan’s maritime security in the Indian Ocean region (IOR). This study focuses on these aspects, first and foremost, the significance of maritime security and strategies in the Indian Ocean, as well as the implications for Pakistan. Second, the policy options available to Pakistan to respond to the strategic calculus of the maritime strategy domain as well as the security domain in the Indian Ocean Region. For the same purpose, Rational Choice Theory, a realist theoretical perspective, has been applied to investigate the methods and techniques used in the conceptualization of the terms maritime strategy and security. Furthermore, qualitative content analysis has been used for doctrines and data analysis. Finally, the study attempts to investigate the strategic and security interests that may become the real impediment to sustaining long-term peace and stability as a result of regional opposition forces. Furthermore, the competitive nature cannot be glossed over for the sake of oversimplification.